Pengaruh Dimensi Experiential Marketing Terhadap Kepuasan Pelanggan di Mulyo Redjo Jombang - Farid Isnan Aziz; Tri Sudarwanto (Prodi Manajemen Fakultas Ekonomi Universitas Hasyim Asy'ari Tebuireng Jombang, 2020)
The purpose of this research is to examine the presence or absence of influence between sense, feel, think, act, and relate to customer satisfaction at Mulyo Redjo Jombang. The method used in this study is a quantitative research method and uses a causal or causal approach. With a sample size of 100 respondents is using non probability sampling techniques through the Purposive Sampling method. The results of the study show that: (1) Sense partially influences customer satisfaction at Warung Lesehan Mulyo Redjo Jombang, (2) Feel has no partial effect on customer satisfaction at Warung Lesehan Mulyo Redjo Jombang, (3) Think partially influences customer satisfaction at Warung Lesehan Mulyo Redjo Jombang, (4) Act partially influences customer satisfaction at Warung Lesehan Mulyo Redjo Jombang, (5) Relate does not have a partial effect on customer satisfaction at Warung Lesehan Mulyo Redjo Jombang, (6) Sense, feel, think, act, and relate simultaneously affect customer satisfaction at Warung Lesehan Mulyo Redjo Jombang.